PECULARITIES OF INDIGENIZATION OF ADMINISTRATIVE AND CULTURAL INSTITUTIONS OF KABARDINO-BALKARIA IN THE LIGHT OF NEWLY FOUND ARCHIVAL DOCUMENTS - H. B. MAMSIROV; A. A. LOOV (Кавказология, 2021)
The problems of indigenization in the North Caucasus in domestic historiography are considered in the chronological framework of 1920-1930., although these processes really began in the imperial period. After the end of the Caucasian war, the royal government is looking for ways to adapt the mountain peoples into the Russian socio-cultural space, turning the region that absorbing huge material and human resources to the region enriching the country.  The imperial experience of managing the region in the end led to awareness of the need to attract the authorities of representatives of the elite from the number of indigenous people. The Bolsheviks took into account the mistakes of their predecessors, and were able to give acceleration to the pace of integration of the Highlanders to the Soviet social and cultural space. They did not fail to take advantage of the experience of the imperial administration in terms of attracting representatives of the autochthonous population into local governments. At the same time, without becoming his class approach, the Bolsheviks opened access to the social elevators to most Highlanders, which cut off representatives of the pre-revolutionary elite. In modern Russia, against the background of strengthening the challenges of globalization, leveling ethnic cultures, individual events of the Soviet nationality are of interest so far, for example, the practice of indigenization. Kabardino-Balkaria more than once turned out to be in the forefront of the Sovietization of the North Caucasus. Part of the events, of course, found the support of the main part of the population. But, in most of them, the population participated voluntarily forcibly, as a direct refusal would be more expensive. The article is based on new archival sources identified in the Funds of the State Archives of the Russian Federation (which are submitted below in this issue), documents from other archives and the latest research on the issue. In general, this made it possible to understand the origins of the process in the imperial period, its logical continuation and national-regional features of the implementation of the indigenization policy in the Soviet Kabardino-Balkaria. Multi-valued for the purposes and objectives, methods of implementation and specific results, this policy is characterized by unprecedented efforts to strengthen state and cultural institutions by national personnel.  But much less researchers talk about the shadow side of the problem, which in modern conditions it is necessary to know for accounting in practical activities both positive and negative lessons to solve the Soviet rule of tasks associated with the national issue.